Assessment of Meat Quality and Shelf Life from Broilers Fed with Different Sources and Concentrations of Methionine - Antonia Albrecht; Martin Hebel; Céline Heinemann; Ulrike Herbert; Dennis Miskel; Behnam Saremi; Judith Kreyenschmidt (Journal of Food Quality)
A trial with different concentrations of DL-methionine (DLM) and DL-2-hydroxy-4-methylthiobutanoic acid (DL-HMTBA) in broiler feed was performed to investigate their effect on the meat quality parameters and the shelf life of breast fillet. In total, fillets from 210 male broiler chickens (Ross 308) were tested in seven groups with 30 animals each. Three different concentrations (0.04, 0.12, and 0.32%; on an equimolar basis) of either DLM or DL-HMTBA were added to a basal diet, summing up to seven treatment groups. After slaughter, fillets were packed aerobically and stored at 4°C. The investigated parameters comprised measurements of microbial as well as physicochemical parameters, such as pH, drip loss, cooking loss, and color measurements. Additionally, sensory investigations were conducted and shelf life was calculated. Mean pH values were between 6.1 and 6.4. Drip loss values were low, with mean values below 0.4%. The cooking loss ranged between 22% and 28% on average. The fillets showed a normal initial microbial quality (2.5 log10 cfu/g) and spoilage process with microbial counts of 8.5 log10 cfu/g at the end of storage. The study revealed a significant influence of methionine supplementation on the quality of broiler breast meat in comparison with the basal group. Methionine supplementation led to higher pH values and a higher water binding. Higher concentrations of methionine had a positive influence on the water-holding capacity by lowering the cooking loss. The L∗ value showed a significant negative correlation to the methionine concentration supplemented. No differences in physicochemical as well as sensory parameters could be detected between both methionine sources. The fillets showed a normal sensory spoilage process and a shelf life of 6 d. White striping was positively correlated to fillet weight as well as color values and significantly affected the Purchase Decision, the sensory investigation, and thus the shelf life of the samples.